Hypernatremia and hypokalemia with Entrectinib therapy: A case of possible nephrogenic diabetes insipidus. Issue 2 (June 2023) - Fadel, Remy; Tabbara, Jad; Huml, Anne; Nakhoul, Georges; Mehdi, Ali
Introduction: Hypernatremia and hypokalemia have been reported with the use of Tropomyosin Receptor Kinase Inhibitors (TRKI) but the pathophysiology is not clear. We hereby describe a 72-year-old male with metastatic papillary thyroid carcinoma presenting with hypernatremia and hypokalemia after starting Entrectinib therapy. Case description: A 72-year-old male with metastatic papillary thyroid carcinoma was admitted to the hospital for failure to thrive and worsening mental status 6 weeks after starting Entrectinib therapy. He was found to have hypernatremia at 154 mmol/L and hypokalemia at 2.9 mmol/L. Serum and urine osmolalities were 320 and 293 mOsm/kg, respectively with an elevated 24 h urinary potassium of 132 mmol. Polydipsia and polyuria were reported raising the suspicion for underlying diabetes insipidus (DI). Twenty-four hour urine output was around 4.5 L. A DDAVP challenge was performed with no change in hourly urine output and a trivial change in urine osmolality toward 339 mOsm/kg indicating a possible partial nephrogenic DI. Potassium was supplemented and patient was treated with free water enterally and parenterally while stopping Entrectinib therapy. One week later, a water deprivation test failed to elicit a hypernatremic response. Unfortunately, urine osmolality variations with water deprivation were not checked but urine volumes dropped significantly suggesting resolution of presumed nephrogenic DI. Conclusion: Hypernatremia has been reported with Tyrosine Kinase Inhibitors but no pathophysiology has been proposed. Hypokalemia however has not been reported. This case reports hypokalemia and hypernatremia in association with Entrectinib therapy with renal potassium wasting and partial nephrogenic as possible pathophysiologic bases respectively. These pathologies seem to be reversible with drug cessation. With the growing use of targeted therapies in oncology and beyond, it seems prudent to better understand the unique electrolyte and water balance abnormalities that might occur so that patients can be counseled and managed appropriately.